2016
DOI: 10.1016/j.molcel.2016.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Mediator Undergoes a Compositional Change during Transcriptional Activation

Abstract: Mediator is a transcriptional co-activator recruited to enhancers by DNA-binding activators, and it also interacts with RNA polymerase (Pol) II as part of the preinitiation complex (PIC). We demonstrate that a single Mediator complex associates with the enhancer and core promoter in vivo, indicating that it can physically bridge these transcriptional elements. However, the Mediator kinase module associates strongly with the enhancer, but not with the core promoter, and it dissociates from the enhancer upon dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
141
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(164 citation statements)
references
References 58 publications
22
141
0
Order By: Relevance
“…Recent reports in yeast demonstrate that Mediator kinase activity and subsequent dissociation of its kinase submodule is required for Mediator release from TF-bound enhancers to trigger transcriptional initiation at proximal promoters (20,21). We were somewhat surprised that Cdk8-transgenic lysates showed relatively little increase in total phosphorylation and no discernible difference in the ratio of phosphorylated to total levels of known Cdk8 targets Smad2 or Stat1.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Recent reports in yeast demonstrate that Mediator kinase activity and subsequent dissociation of its kinase submodule is required for Mediator release from TF-bound enhancers to trigger transcriptional initiation at proximal promoters (20,21). We were somewhat surprised that Cdk8-transgenic lysates showed relatively little increase in total phosphorylation and no discernible difference in the ratio of phosphorylated to total levels of known Cdk8 targets Smad2 or Stat1.…”
Section: Discussionmentioning
confidence: 82%
“…Of the approximately 30 subunits within the Mediator complex, the kinase submodule consisting of Mediator-13 (Med13), Med12, cyclin-dependent kinase 8 (Cdk8), and cyclin C represents an appealing starting point for investigation of global cardiac transcription mechanisms. This submodule regulates gene expression through its dynamic association with the Mediator core complex and through its Cdk8 activity (19)(20)(21). We recently reported the novel observation that cardiac Med13 functions to regulate whole-body energy homeostasis (22,23) and that Med1 is essential in postnatal and adult cardiomyocytes (24); however, the function of Mediator kinase activity has yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…The Mediator complex is an evolutionarily conserved transcriptional activator composed of three stable modules – the Head, Middle and Tail (Figure 3A) – and one detachable, cell cycle specific module (Cyclin Kinase Module, not crystallized) (Nozawa et al, 2017; Tsai et al, 2017). Recent biochemical and genetic studies have demonstrated that the Head, Middle and Tail modules exhibit differential genomic targeting and have specialized roles in the context of Mediator complex global function (Jeronimo et al, 2016; Petrenko et al, 2016). Depletion of subunits belonging to the Head, Middle and Tail modules results in distinct cell fitness effects across cancer cell lines (Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
“…Mediator can physically bridge enhancer-bound transcription factors and the promoter-bound transcription apparatus (Allen and Taatjes, 2015; Jeronimo et al, 2016; Kagey et al, 2010; Malik and Roeder, 2010; Petrenko et al, 2016). Cohesin is loaded at active enhancers and promoters by the Mediator-associated protein NIPBL and may transiently stabilize enhancer-promoter interactions (Kagey et al, 2010; Schmidt et al, 2010).…”
Section: Introductionmentioning
confidence: 99%